Deconstructing the 4-h rule for access to emergency care and putting patients first. - Scott, Ian; Sullivan, Clair; Staib, Andrew; Bell, Anthony (Australian Health Review, 2018)
Evidence suggests improved outcomes for patients requiring emergency admission to hospital are associated with improved emergency department (ED) efficiency and lower transit times. Factors preventing timely transfers of emergency patients to in-patient beds across the ED–in-patient interface are major causes for ED crowding, for which several remedial strategies are possible, including parallel processing of probable admissions, direct-to-ward admissions and single-point medical registrars for receiving and processing all referrals directed at specific speciality units. Dynamic measures of ED overcrowding that focus on boarding time are more indicative of EDs with exit block involving the ED–in-patient interface than static proxy measures such as hospital bed occupancy and numbers of ED presentations. The ideal 4-h compliance rate for all ED presentations is around 80%, based on a large retrospective study of more than 18 million presentations to EDs of 59 Australian hospitals over 4 years, which demonstrated a highly significant linear reduction in risk-adjusted in-patient mortality for admitted patients as the compliance rate for all patients rose to 83%, but was not confirmed beyond this rate. Closely monitoring patient outcomes for emergency admissions in addition to compliance with time-based access targets is strongly recommended in ensuring reforms aimed at decongesting EDs do not compromise the quality and safety of patient care.